2007
DOI: 10.1093/geronb/62.2.p78
|View full text |Cite
|
Sign up to set email alerts
|

Lateralized Readiness Potentials Reveal Motor Slowing in the Aging Brain

Abstract: Older adults consistently show slower reaction times (RTs) to the onset of motion. Both cognitive slowing and motor slowing have been suggested as causes of this effect. The lateralized readiness potential (LRP) of the electroencephalogram can be used to separate perceptual and decision processes from motor programming and execution as causes of RT differences. We used the LRP to discern the origin of slowing in RT to motion onset that occurs in elderly individuals. After the onset of motion in a visual displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
49
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 31 publications
8
49
1
Order By: Relevance
“…The latter effect is known as "the complexity effect", which indicates that slowing is not constant across tasks but increases with task complexity (see Salthouse, 2000 for a review). Other studies have shown an increase of LRP amplitudes in older, compared to younger, adults despite a lack of difference between groups in the onset of the LRPs (Roggeveen et al, 2007;Sterr and Dean, 2008), supporting the idea that greater amplitudes might reflect more inhibitory failures.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…The latter effect is known as "the complexity effect", which indicates that slowing is not constant across tasks but increases with task complexity (see Salthouse, 2000 for a review). Other studies have shown an increase of LRP amplitudes in older, compared to younger, adults despite a lack of difference between groups in the onset of the LRPs (Roggeveen et al, 2007;Sterr and Dean, 2008), supporting the idea that greater amplitudes might reflect more inhibitory failures.…”
Section: Introductionmentioning
confidence: 69%
“…The overall alpha level was fixed at 0.05 after the Geisser-Greenhouse correction. Furthermore, given the well-known age-related behavioral slowing (indexed by RTs; i.e., Vallesi et al, 2009) and the slowing of the cognitive processing required by the task (indexed by its electrophysiological marker, the P3 peak latency; i.e., Roggeveen et al, 2007), we explored the relationship between those variables and the BP peak latency, which we considered a sensitive index of executive functions. Thus, correlations (Pearson's r coefficients) were computed, separately for the SRT and the DRT tasks, between age and RT and between RT and P3 and BP latencies, with particular focus on the older group.…”
Section: Discussionmentioning
confidence: 99%
“…Because RT is a good indicator of the functional integrity of the CNS, RT slowing has been associated with age-related decline in central information processing including sensorimotor integration and motor generation (Yordanova, Kolev, Hohnsbein, & Falkenstein, 2004). A number of recent studies have suggested that the major source of slowing with age may be the degradation of motor response generation processes, rather than delays in stimulus processing or response selection (Roggeveen, Prime, & Ward, 2007;Yordanova et al, 2004). In these studies motorrelated potentials of EEG indicated that the RT delay in older adults was associated with mechanisms relating to the activation of contralateral motor areas responsible for triggering the responding effector Yordanova et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recent EEG studies have shown that brain activity related to anticipation, preparation, and/or generation of motor responses is changed in healthy aging (Falkenstein et al 2006;Golob et al 2005;Roggeveen et al 2007;Sailer et al 2000;Sterr and Dean 2008;Yordanova et al 2004). More specifically, Sterr and Dean (2008) showed that increased negativity of contingent negative variations (CNVs) in younger individuals during the preparatory period of a precued choice reaction time (CRT) task was associated with higher recruitment of the frontal brain network and lateralized activation over motor regions, whereas these trends were not seen in older individuals.…”
mentioning
confidence: 99%
“…More specifically, Sterr and Dean (2008) showed that increased negativity of contingent negative variations (CNVs) in younger individuals during the preparatory period of a precued choice reaction time (CRT) task was associated with higher recruitment of the frontal brain network and lateralized activation over motor regions, whereas these trends were not seen in older individuals. Observations from studies using lateralized readiness potentials (LRPs) and/or event-related potentials (ERPs) have suggested that behavioral slowing is mainly due to slower response generation, rather than response selection and stimulus processing (Falkenstein et al 2006;Roggeveen et al 2007;Yordanova et al 2004). Specifically, behavioral slowing in elderly individuals may be due to an enhanced and prolonged activity in the contralateral motor cortex during response generation (Falkenstein et al 2006;Yordanova et al 2004).…”
mentioning
confidence: 99%